Particulate and ion forms of Cobalt-Chromium challenged preosteoblasts promote osteoclastogenesis and osteolysis in a murine model of prosthesis failure - Yang, Shuye (J Biomed Mater Res A, 2018)
This study investigated the interactive behavior of the particulate and ion forms of Cobalt-Chromium (Co-Cr) alloy challenged preosteoblasts during the process of prosthetic implant loosening. Preosteoblasts were challenged with Co-Cr particles or Co(II) ions for 72 hours, followed by the proliferation and PCR assays. For in vivo test, a titanium-pin was implanted into proximal tibia of SCID mice to mimic knee replacement. Co-Cr particles or Co(II) ion challenged preosteoblasts (5×10(5)) were intra-articularly injected into the implanted knee. The animals were sacrificed 5 weeks post-op, and the prosthetic knees were harvested for biomechanical pin-pullout testing, histological evaluations, and microCT assessment. In vitro study suggested that Co-Cr particles and Co(II) ions significantly suppressed the proliferation of preosteoblasts in a dose-dependent manner. RT-PCR data on the challenged cells indicated over-expression of receptor activator of nuclear factor kappa-B ligand (RANKL) and inhibited osteoprotegerin (OPG) gene expression. Introduction of the differently challenged preosteoblasts to the pin-implant mouse model resulted in reduced implant interfacial shear strength, thicker peri-implant soft-tissue formation, more TRAP+ cells, lower bone mineral density and bone volume fraction. In conclusion, both Co-Cr particles and Co(II) ions interfered with the growth, maturation and functions of preosteoblasts, and provides evidence that the metal ions as well play an important role in effecting preosteoblasts in the pathogenesis of aseptic loosening.